KEPEMIMPINAN KEPALA SEKOLAH MADRASAH UNTUK MENINGKATKAN KINERJA GURU - Rafiq Mubarak; Achadi Budi Santosa (Prodi PGMI STPI Bina Insan Mulia Yogyakarta, 2020)
The purpose of research is to describe the leadership of madrasah headmaster to improve teacher performance. This research method uses qualitative methods and the research subjects are madrasah school principals and teachers. Data collection is done with interviews, observation and documentation. The data analysis uses miles & huberman analysis models with the sequence of data collection, data reduction, data presentation, and deduction. This research shows (1). The importance of the leadership role of the madrasah headmaster to improving teacher performance through a teacher's professional improvement by attending a seminar, subject teachers' deliberations (MGMP) (2). The leadership of the madrasah school principal in creating a conducive cultural climate of madrasah school which encourages teachers in teaching students to improve their character and moral of the learners.